Analisis Implementasi Metode Pembelajaran Literasi Numersi pada Anak Usia Dini di PAUD Mathla UI Anwar - Dinda Putri Ainiyah; Elsy Virjita; Imely Banjarnahor; Nabila Simamora; Angel Marantika Siregar; Trisnawati Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Numeracy literacy is one of the basic competencies that need to be developed from an early age as a foundation for children in understanding the concepts of numbers, patterns, measurement, and solving simple problems in daily life. This study aims to analyze the application of numeracy literacy learning methods for early childhood at PAUD Humairah. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that teachers implement various learning methods such as play methods, demonstrations, question-and-answer sessions, singing, and simple projects to develop children's numeracy literacy skills. Supporting factors for the implementation of learning include teacher competence, the availability of learning media, and parental support. Meanwhile, inhibiting factors include the limitations of learning facilities and differences in children's abilities. The results of the study are expected to can be used as material for evaluation and development of numeracy literacy learning in early childhood education.